Adaptation of the Bergen Social Media Addiction Scale (BSMAS) in Spanish - Copez-Lonzoy, Anthony (2023)
The impact of social networks on people's daily lives is worrisome, particularly in adolescents and young people, who seem to exceed the limits of normal use. Constant excessive use can lead to pathological behaviors linked to social media addiction (SMA). Our objectives were to 1) adapt the Bergen Social Media Addiction Scale (BSMAS) to Spanish and 2) evaluate its psychometric properties in a young population. The BSMAS was adapted to Spanish, involving experts on social media addiction and people from the target population during the adaptation process. For the psychometric evaluation, 650 Peruvian college students responded to the Spanish version (53.5 % women aged 18 to 40, M = 21.5 SD = 2.7). The one-dimensional measurement model proposed for the original BSMAS was confirmed for our version (X2(9) = 23.9315, CFI = 0.994, TLI = 0.990, SRMR = 0.032, RMSEA = 0.061). The reliability was good (α = 0.863; 95 % CI: 0.848–0.870; ω = 0.864; 95 % CI: 0.846–0.844), and the measurement invariance was confirmed for sex and age by fitting models. The concurrent validity with external social media addiction and mental health indicators was also confirmed. This study provides new and relevant information on the BSMAS validity and allows its application to Spanish-speaker college students from Peru and similar countries.